Air Transport Sector after 2010: A Modified Market and Ownership Structure - Hilde Meersman; Eddy van de Voorde; Thierry Vanelslander (European Journal of Transport and Infrastructure Research, 2008)
This paper outlines the future possible scenarios that the air transport sector may evolve into after 2010, starting from the most important trends from the past and actual market developments. A big market shift was the liberalization which was introduced in the 1990’s, which led to an improved capacity utilisation for both passengers and freight. The impacts on and reactions from airlines have been different over continents and over types of companies. Furthermore, increasing importance has been attached to yield, pushing airline companies towards various forms of co-operation and integration. In the future, some more developments may change the air transport market. First, we may expect a stronger split between traditional air transport and niche markets. Second, privatisation may be strengthening, not only among airlines, but also in airports. Third, mergers and acquisitions may drastically shift the market and lead to new competitive balances. Fourth, the Southwest model, based on low costs and low fares, is likely to survive, although some maturity is observed, but new products emerge. Fifth, the relatively large number of bankruptcies is a new phenomenon for air transport. Carriers not belonging to strategic alliances turn out to be more likely victims. Sixth, increasing aggressiveness in company strategies and reactions is observed, including price cuts but also hostile takeover bids. Seventh, privatization is gaining pace, while on the other hand governments will continue to be an important player, be it on a different front: as infrastructure providers, market regulators and environmental protectors. Eight, air freight is still a growing market, with an own network which is gradually developing, next to the passenger network. A ninth and last tendency is the entry of more foreign and private equity capital, the latter of which may sometimes be at odds with the long-term strategies of the sector.